Identification of TRAILApo2L as a novel therapy targeting HIV reservoirs and the development of antiapoptotic peptides for protection from HIV induced cell death - Lum, Julian J (University of Ottawa (Canada), 2003)
Apoptosis of CD4 T cells is the major immunological feature of HIV-1 disease. Despite the profound benefits of protease inhibitor based therapy, complete and absolute eradication of HIV is elusive. The main reason is the development of viral reservoirs including HIV infected macrophages and latently infected resting memory CD4 T cells which are refractory to all current HIV drugs. With concerns of toxicity and drug resistance, novel strategies specifically directed at reservoirs are clearly required. Dysregulation of death inducing ligands is a common characteristic of HIV infection. Here, we demonstrate altered regulation of TRAIL/Apo2L and its receptors in cells from infected patients. Moreover, in vitro treatment of latently infected resting memory cells with TRAIL/Apo2L significantly reduces the viral reservoir burden, in some cases to undetectable levels. This indicates that TRAIL/Apo2L possesses anti-HIV activity and implies a novel therapeutic strategy for elimination of HIV. Activation of natural killer cells with IL-15 induces a substantial increase in TRAIL/Apo2L which results in enhanced TRAIL/Apo2L specific lysis and killing of cellular reservoirs of HIV. We also suggest a possible mechanism whereby cells resistant to TRAIL/Apo2L killing acquire a sensitive phenotype, through a direct interaction with the chemokine receptor CXCR4. Finally, we show that TRAIL/Apo2L may be a regulator of inflammatory responses. HIV-1 Vpr is an important accessory gene which contributes to the destruction of CD4 T cells. Analysis of long-term asymptomatic patients found a high frequency of a specific polymorphism within a region responsible for activating mitochondria death signals. This mutation, R77Q had a diminished ability to mediate death of T cells when compared to the wildtype virus suggesting that other mutations may possess dominant negative activity. In this case, we generated a peptide termed DN2 that blocked apoptosis irrespective of HIV both in vitro and in vivo. The generalized ability of this peptide to inhibit apoptosis suggests it may prove useful for diseases where there is evidence of excessive apoptosis.
Keywords: Biology, Molecular.; Biology, Cell.; Health Sciences, Immunology.